Hemorrhagic Shock: A Meckel Diverticulum Rare Presentation - Morgado, Mariana (2020)
Meckel’s diverticulum is the most frequent congenital malformation of the gastrointestinal tract. The diagnosis is challenging and often incidental, because it is infrequently symptomatic. Symptomatic presentation is more common in the first decade of life and complications are more prevalent in the first 2 years, decreasing afterwards. Complications include ulceration with haemorrhage, perforation, bowel occlusion and neoplasm. We report a clinical case of a rare Meckel’s diverticulum presentation, in an adolescent, with haemorrhagic shock and we make a brief literature review.